In Vitro Antimicrobial Efficacy Assessment of Ethanolic, Aqueous, and Dual Solvent Extracts of Mushroom Ganoderma lucidum: Genomic and Morphological Analysis - Ewunkem Akamu; Lydia Merrills; Zahirah Williams; Brittany Justice; Uchenna Iloghalu; Vera Williams; Dinesh Singh (Antibiotics)
Background: Infectious diseases caused by bacteria are life-threating and are among the major causes of death in the world. Antibiotics have offered humans a new approach to infection control. Antibiotics are reckoned as the “magic bullets” for the fight against bacterial infections, therefore increasing life expectancy and decreasing mortality and morbidity. However, the overuse of antibiotics has resulted in the persistent growth of resistant bacterial pathogens. New antimicrobial approaches against resistant pathogens are being examined. Mushrooms seem to be a promising, and possibly more efficient, alternative method to that of conventional antimicrobials. This work aimed to investigate the phytochemical constituents and antimicrobial potential of ethanolic, aqueous, and dual solvent extracts of mushroom Ganoderma lucidum. Methods: The antimicrobial studies were carried out by broth dilution against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli. The present research work was also carried out to examine genomic changes associated with ethanolic, aqueous, and dual solvent extracts of G. lucidum in S. aureus and E. coli. Results: Our data quantitatively showed that all the extracts of G. lucidum were found to exhibit various degrees of antimicrobial effects against S. aureus and E. coli where the ethanolic extract exhibited the most potent antimicrobial activity. SEM images showed untreated cells with normal cell characteristics while, after treatment with extracts of G. lucidum, cells appeared damaged with irregular cell surfaces and cell wall defacement. The results of HPLC analysis showed that ethanolic and aqueous extract of G. lucidum consisted of beta[1-3] glucans, ganoderic acid, and triterpenoids. Genomic analysis identified selective sweeps in several genes associated with growth, biosynthesis transport, and stress. Conclusions: This study concludes that the extracts of three solvents of G. lucidum have antimicrobial activity against infectious bacteria causing morphological changes and the acquisition of mutations in genes. Therefore, the extracts of G. lucidum may be candidates for preventing infectious diseases in the future. Ganoderma lucidum mushroom is therefore a reliable source of antimicrobial agent that can be used against infectious diseases.